Performance of beef cattle bulls in feed lots and fed on diets containing enzymatic complex - Leonardo Guimarães de Oliveira; Reginaldo Nassar Ferreira; João Teodoro Padua; Cirano José Ulhoa; Cristine dos Santos Settimi Cysneiros; Emmanuel Arnhold (Acta Scientiarum. Animal Sciences, 2015)
Current paper evaluates the performance of confined beef cattle supplemented with amylolytic enzyme complex produced by fungus Aspergillus awamori and a commercial product containing multienzyme complex, yeast and MOS. Treatments comprised control (basal diet composed of 16% Mombasa grass silage, 66% ground corn, 3% vitamin nuclear mineral and 15% cottonseed meal), amylase treatment (control diet with the addition of 48.7 saccharifying units kg-1 diet) and compound treatment (control diet with the addition of enzymatic complex composed of 83.2 saccharifying units, 8.8 fibrolytic units, 0.05 g of mannan oligosaccharides and 0.2 g of inactivated yeast Kg-1 of the dry matter diet). The addition of products did not significantly increase daily weight gain, intake, feed conversion and carcass yield of cattle. There was no difference between in vitro digestibility of dry matter (IVDMD) in the diets. The percentage of residual fecal starch was not influenced by exogenous amylolytic enzymes of amylase and compound treatments. The tested products were not able to improve animal performance.